Retinal glia in myopia: current understanding and future directions - Chen, Pengfan; Ji, Jing; Chen, Xinyi; Zhang, Jiali; Wen, Xiangyi; Liu, Longqian (Frontiers in Cell and Developmental Biology, 2024)
Myopia, a major public health problem, involves axial elongation and thinning of all layers of the eye, including sclera, choroid and retina, which defocuses incoming light and thereby blurs vision. How the various populations of glia in the retina are involved in the disorder is unclear. Astrocytes and Müller cells provide structural support to the retina. Astrogliosis in myopia may influence blood oxygen supply, neuronal function, and axon diameter, which in turn may affect signal conduction. Müller cells act as a sensor of mechanical stretching in myopia and trigger downstream molecular responses. Microglia, for their part, may exhibit a reactive morphology and elevated response to inflammation in myopia. This review assesses current knowledge about how myopia may involve retinal glia, and it explores directions for future research into that question.